Flow regimes in T-shaped micro-mixers. (8th May 2015) - Andreussi, Tommaso; Galletti, Chiara; Mauri, Roberto; Camarri, Simone; Salvetti, Maria Vittoria
Abstract : Highlights: DNS of laminar mixing in T-shaped micro-devices with different aspect ratios k . Five regimes: symmetric/asymmetric steady, asymmetric/symmetric unsteady, chaotic. Transitions from steady to unsteady and chaotic regimes depend on k . No steady asymmetric (engulfment) regime for k ≥ 2. Strouhal number of unsteady flows depends on k . Abstract: The different flow regimes occurring in T-mixers are investigated by means of direct numerical simulations. Three different values of the aspect ratio of the inlet channels, κ i, that is their width to height ratio are considered, namely κ i = 0.75, 1 and 2. For the configurations with κ i = 0.75 and 1, the same behavior as previously described in the literature, is found. In particular, as the Reynolds number is increased, the flow evolves from vortical to engulfment steady regimes, then to unsteady asymmetric and symmetric periodic regimes, until, finally, it becomes chaotic. All the critical values of the Reynolds number, at which the transitions between the different regimes occur, are found to be very similar for κ i = 0.75 and 1, while some differences are highlighted in the vorticity dynamics and characteristic frequencies of the unsteady regimes. The observed scenario is completely different for κ i = 2. Indeed, in this case, the flow evolves directly from the vortical regime to an unsteady symmetric behavior, with a vorticity dynamics that is significantly different from those observed for the other aspect ratios.